2013
DOI: 10.1038/nature12043
|View full text |Cite
|
Sign up to set email alerts
|

Landscape of the PARKIN-dependent ubiquitylome in response to mitochondrial depolarization

Abstract: The PARKIN (PARK2) ubiquitin ligase and its regulatory kinase PINK1 (PARK6), often mutated in familial early onset Parkinson’s Disease (PD), play central roles in mitochondrial homeostasis and mitophagy.1–3 While PARKIN is recruited to the mitochondrial outer membrane (MOM) upon depolarization via PINK1 action and can ubiquitylate Porin, Mitofusin, and Miro proteins on the MOM,1,4–11 the full repertoire of PARKIN substrates – the PARKIN-dependent ubiquitylome - remains poorly defined. Here we employ quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

29
895
3
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 892 publications
(930 citation statements)
references
References 33 publications
29
895
3
3
Order By: Relevance
“…8 This is in agreement with the observed increase in parkin levels upon Rpn13 silencing (Fig. 5A), increased parkin stability upon removal of its Ubl domain (58), and lack of strong increase in proteasomal binding to parkin lacking Ubl domain upon mitochondrial depolarization (56). Rpn13 might also regulate the amount of parkin depending on the availability of parkin substrates and might recruit parkin for its subsequent degradation when its substrates are not available or are present at low amounts.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…8 This is in agreement with the observed increase in parkin levels upon Rpn13 silencing (Fig. 5A), increased parkin stability upon removal of its Ubl domain (58), and lack of strong increase in proteasomal binding to parkin lacking Ubl domain upon mitochondrial depolarization (56). Rpn13 might also regulate the amount of parkin depending on the availability of parkin substrates and might recruit parkin for its subsequent degradation when its substrates are not available or are present at low amounts.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, at least for these substrates, parkin binding to the proteasome may not be essential for turnover. However, the role of parkin in turnover of other substrates could not be excluded, and we therefore tested the effect of HEK293T knockdown in the context of mitophagy, where the role of parkin has been well established (13,22,24,56). Indeed, Rpn13 knockdown caused a delay in the clearance of the outer mitochondrial protein TOM20 upon CCCP treatment.…”
Section: Discussionmentioning
confidence: 99%
“…An unanswered question is why Parkin E3 ligase activity is required for mitochondrial translocation. In our studies, we found that, unlike the WT RBR domain, a mitochondrially- [44]. Another recent study reported a new function for Parkin showing that in response to cellular stress, Parkin is recruited to the linear ubiquitin chain assembly complex, and increases linear ubiquitylation of NEMO, a process that is critical for the activation of the NF-κB pathway [45].…”
Section: Parkin Binds K63-linked Ubiquitin Chainssupporting
confidence: 53%
“…Moreover, the regulation of FBXW7 by Parkin suggests a putative feedback loop providing regulatory countermeasures. Although further work will be required to elucidate these mechanisms, additional evidence supports a role for Parkin in regulating lipid metabolism; Parkin has been reported to ubiquitinate and stabilize both the SREBP target FASN and the fatty acid transporter CD36 (9,28). Finally, the identification of SREBF1 as a GWAS risk locus for sporadic PD (10), coupled with our findings that this pathway regulates mitophagy, provides further support that the causes of sporadic and autosomal recessive PD may share some mechanistic overlap.…”
Section: Discussionmentioning
confidence: 99%
“…Following loss of ΔΨm, PINK1 accumulates on the outer mitochondrial membrane (OMM) (3,4), where its kinase activity stimulates the translocation of Parkin (5, 6) from a diffuse cytoplasmic distribution to accumulate on mitochondria (7). The recruitment of Parkin to mitochondria results in the ubiquitination of multiple proteins (8,9). These include several proteins on the OMM that regulate mitochondrial dynamics, such as Mfn and Miro.…”
mentioning
confidence: 99%